1998
DOI: 10.1046/j.1365-2141.1998.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells derived from bone marrow and CD34+ selected blood progenitor cells of myeloma patients, cultured in serum‐free media, do not contain the Kaposi sarcoma herpesvirus genome

Abstract: The aim of our study was to test if dendritic cells contain the KSHV genome. CD34+ peripheral blood progenitor cells (PBPC) and bone marrow mononuclear cells were cultured in X-VIVO 15 medium supplemented with GM-CSF and TNF-alpha in gas-permeable containers. Dendritic cells were identified morphologically and immunophenotypically. The KSHV genome was not identified in any of the cases using a nested primer PCR approach. Serological analysis corroborated the molecular findings: no antibodies for KSHV were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…Furthermore, no statistically significant differences between MM patients and blood donors were observed in the frequency of HHV-8 seropositivity using an IFA assay 76 . Similar results have also been found by others [93][94][95][96][97] . Any significance of HHV-8 in the etiology of MM thus remains unclear.…”
Section: Multiple Myelomasupporting
confidence: 81%
“…Furthermore, no statistically significant differences between MM patients and blood donors were observed in the frequency of HHV-8 seropositivity using an IFA assay 76 . Similar results have also been found by others [93][94][95][96][97] . Any significance of HHV-8 in the etiology of MM thus remains unclear.…”
Section: Multiple Myelomasupporting
confidence: 81%
“…Serologic studies have been almost uniform in their findings, demonstrating that patients with multiple myeloma lack antibodies to KSHV (44,188,200,224,256,290 This lack of reactivity is not due to generalized immunosuppression, since antibodies to other more ubiquitous herpesviruses, such as EBV, HHV-6, and cytomegalovirus, are easily detectable in these patients by using comparable methodologies. Since MGUS patients are known to develop multiple myeloma or other lymphoproliferative diseases within 10 to 20 years (152), the serum of MGUS patients, some of whom later developed multiple myeloma, was tested for the presence of HHV-8 IgG antibodies to both lytic and latent antigens (2).…”
Section: Multiple Myeloma and Hhv-8 Infectionmentioning
confidence: 98%
“…Multiple studies have been published since, with conflicting results. Several additional independent laboratories confirmed the specific presence of KSHV DNA sequences in multiple myeloma biopsies (4,60,238 However, other investigators have been unable to confirm this association when looking for KSHV DNA by PCR in bone marrow biopsies and/or dendritic cell cultures from bone marrow or peripheral blood (35,44,69,188,200,218,224,229,278,279,282,296).…”
Section: Multiple Myeloma and Hhv-8 Infectionmentioning
confidence: 99%
“…This finding was confirmed in some reports Chauhan et al, 1999) but not in others (MacKenzie et al, 1997;Parravicini et al, 1997;Mitterer et al, 1998). HHV8 encodes a homologue of the cytokine IL-6, known to be required for MM pathogenesis Burger et al, 1998), and expression of the viral IL-6 has been reported in dendritic cells of MM patients, providing a plausible hypothesis on a mechanism whereby HHV8 might be involved in MM pathogenesis.…”
mentioning
confidence: 72%